Mind the gap: female coaches in hollywood sports films. Issue 1 (25th March 2016) - Bonzel, Katharina
Abstract: In the summer of 2015, the NFL employed both their first female professional referee and their first female coach, while the NBA now has two female coaches in its employment. Representations of female coaches in contemporary popular sports films are, however, virtually non-existent. No mainstream sports film has featured a female coach as a central character since 1996. The overwhelming majority of sports films are about male coaches coaching male athletes. Women coaching men, in particular in professional sports, remain an often uncrossed boundary in films about coaching. This study analyses the depiction of female coaches in three Hollywood films – Wildcats (1986), Eddie (1996) and Sunset Park (1996) – arguing that while these films may well have feminist intentions, they overwhelmingly conform to stereotypical and essentialist ideas of the "woman as coach" trope.